1973
DOI: 10.1084/jem.138.6.1379
|View full text |Cite
|
Sign up to set email alerts
|

Synergy During in Vitro Cytotoxic Allograft Responses

Abstract: The importance of cell interaction among lymphoid cells in the development of immune responses is well established. In humoral responses bone marrowderived (B) lymphocytes are recognized to be precursors of the cells that release serum antibody (1-4). Thymus-derived (T) lymphocytes, on the other hand, do not develop into antibody-forming cells (5) but play an important role in primary antibody responses by cooperating with B cells (6, 7).In contrast, cellular immunity is thought to be mediated by T lymphocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1974
1974
1978
1978

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…As there was no enhancement of FPR to MHSA in 6-mo-old mice, which had been thymectomized at less than 2 wk of age, a period of time may be required to develop effector T-cell function in the peripheral lymphoid system under the state of a functioning thymus. In CMI, such long-lived effector T cells were also observed in development of GVH response (3,4,41) in vivo and in expression of T-cell-mediated cytotoxicity (12) and MLR (8) in vitro.…”
Section: Effect Of Aging Adult Thymectomy and Additionally Transfermentioning
confidence: 93%
See 1 more Smart Citation
“…As there was no enhancement of FPR to MHSA in 6-mo-old mice, which had been thymectomized at less than 2 wk of age, a period of time may be required to develop effector T-cell function in the peripheral lymphoid system under the state of a functioning thymus. In CMI, such long-lived effector T cells were also observed in development of GVH response (3,4,41) in vivo and in expression of T-cell-mediated cytotoxicity (12) and MLR (8) in vitro.…”
Section: Effect Of Aging Adult Thymectomy and Additionally Transfermentioning
confidence: 93%
“…sion in vitro have been observed in mixed lymphocyte reactions (MLR) (8)(9)(10)(11) and in cytotoxic allograft responses (12)(13)(14)(15). Delayed hypersensitivity (DH) is an important phenomenon manifested by T-cell activity, yet few papers have discussed such activity.…”
Section: Gershon Et Al (5 6) and By Hardin Et Al (7) T-t-cell Coomentioning
confidence: 99%
“…Recent data from several laboratories (22,23) have shown that synergy results from interactions among thymocytes and peripheral T cells in cellular immunity to transplantation antigens. Our observations are consistent with this emerging concept of T-cell-T-cell interaction in cellular immune responses in the sense that they demonstrate that T lymphocytes may also exert a regulatory influence and suppress CL responses.…”
Section: Characterization Of Conmentioning
confidence: 99%
“…Originally, T-T collaboration was thought of in terms of synergy between thymocytes and lymph node cells but the functional contributions of each were not characterized (1,2) . The participation of two collaborating cell types in the induction of a cytotoxic response was also shown by later work demonstrating that the cytotoxic T precursor had Ly2,3 antigens on its surface and was apparently specific for H-2K and D region encoded determinants although the helper/amplifier cell had Lyl antigen and appeared to be specific for determinants encoded in the I region of the H-2 gene complex (3) .…”
mentioning
confidence: 99%